2012
DOI: 10.1016/j.apm.2011.11.004
|View full text |Cite
|
Sign up to set email alerts
|

MHD oblique stagnation-point flow of a micropolar fluid

Abstract: Abstract. The steady two-dimensional oblique stagnation-point flow of an electrically conducting micropolar fluid in the presence of a uniform external electromagnetic field (E 0 , H 0 ) is analyzed and some physical situations are examined. In particular, if E 0 vanishes, H 0 lies in the plane of the flow, with a direction not parallel to the boundary, and the induced magnetic field is neglected. It is proved that the oblique stagnationpoint flow exists if, and only if, the external magnetic field is parallel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 18 publications
1
26
0
Order By: Relevance
“…The effect of different emerging parameters on the temperatures profiles are displayed in Figs. [15][16][17][18]. It is obvious from these figures.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The effect of different emerging parameters on the temperatures profiles are displayed in Figs. [15][16][17][18]. It is obvious from these figures.…”
Section: Resultsmentioning
confidence: 90%
“…Ishak [15] studied the thermal boundary layer flow over stretching sheet in a micropolar fluid with radiation effect. More recently, Borrelli et al [16] discussed the MHD oblique-stagnation flow of a micropolar fluid. They solve the resulting problem numerically and demonstrated that oblique stagnation point flow exist if and only if the magnetic field is parallel to streamline.…”
Section: Introductionmentioning
confidence: 98%
“…It is recognized that the outer flow, in terms of ψ, is the partnership of basic shear flow and the orthogonal stagnation flow as [51]…”
Section: Basic Equationsmentioning
confidence: 99%
“…Recently, Rosali et al [15] analyzed the flow of micropolar fluid past a permeable stretching/shrinking sheet in a porous medium. Engineers and scientists have been engaged in the research of flows of micropolar fluids with different aspects [16][17][18][19][20][21]. Bhattacharyya et al [22] reported the radiation effect on the steady flow of micropolar fluid past a shrinking sheet.…”
Section: Introductionmentioning
confidence: 98%